EFEKTIFITAS KOMBINASI TEKNIK SLOW DEEP BREATHING DAN TEKNIK EFFLEURAGE TERHADAP INTENSITAS NYERI DISMENOREA - Indah ' Astria; Sri ' Utami; Wasisto ' Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2016)
Abstract The aim of this research was to determined the effect combination of slow deep breathing technique and effleurage technique for dysmenorrhoea pain intensity. The design of this research was “Quasy experiment” with “Non-equivalent control group” approach, that divided into experiment group and control group. The research was conducted on students who attend school in “SMA Negeri 6 Kundur Kepulauan Riau”. The total sample were 30 students who fit the inclusion criteria and chosen by simple random sampling technique. Measuring instrument was observation sheet that used in both groups. The analysis used univariate and bivariate analyzes by using independent and dependent sample t test. The result showed with p value (0,000) < α (0,05). It means that combination of slow deep breathing technique and effleurage techniques was effective for reduce dysmenorrhoea pain intensity. Combination of slow deep breathing technique and effleurage technique can reduce dysmenorrhoea pain intensity in non pharmacology which can be practiced independently, thus expected for students who have other members of family or local communities use this techniques for reducing dysmenorrhoea pain intensity.